Asthma Associated Cytokines Regulate the Expression of SARS-CoV-2 Receptor ACE2 in the Lung Tissue of Asthmatic Patients - Saheb Sharif-Askari, Fatemeh; Goel, Swati; Saheb Sharif-Askari, Narjes; Hafezi, Shirin; Al Heialy, Saba; Hachim, Mahmood Yaseen; Hachim, Ibrahim Yaseen; Mahboub, Bassam; Salameh, Laila; Abdelrazig, Mawada; Elzain, Eman Ibrahim; Al-Muhsen, Saleh; et al. (Frontiers in Immunology, 2022)
Chronic respiratory diseases are associated with severe COVID-19 related illness. As the level of SARS-CoV-2 receptor in lung tissue of asthmatic relative to age, gender, and asthma severity is not known, we hence aimed to determine factors regulating ACE2 lung expressions in these subjects. Therefore, by re-analyzing gene expression data sets of well known asthmatic cohorts we have evaluated the association of ACE2 and TMPRSS2 with age, gender of the asthmatic patients, as well as the type of the underlying lung tissue inflammatory cytokines. Notably, SARS-CoV-2 receptor ACE2 expression was upregulated in the lungs tissue of asthmatics compared to healthy controls. Although a differential expression of this receptor was observed relative to age within the moderate and severe asthma groups, our data suggest that age may not be a key regulatory factor of its expression. The type of tissue inflammation, however, associated significantly with ACE2 and TMPRSS2 expression levels. Following adjusting with patient’s age, gender and oral corticosteroids use, IFN-, IL-8, and IL-19 were associated with increased expression; while IL-4 and IL-13 with lower expression of ACE2 in lung tissue (airway epithelium and/or lung biopsies) of moderate and severe asthmatic patients. IL-19 was associated with ACE2 expression while IL-17 was associated with TMPRSS2 expression in sputum of asthmatic subjects. In vitro treatment of bronchial fibroblasts with IL-17 and IL-19 cytokines confirmed the regulatory effect of these cytokines on SARS-CoV-2 entry genes. Our results suggest that the type of inflammation may regulate ACE2 and TMPRSS2 expression in the lung tissue of asthmatics and may hence affect susceptibility to SARS-CoV-2 infection.